2022
DOI: 10.26668/businessreview/2022.v7i2.414
|View full text |Cite
|
Sign up to set email alerts
|

The Development Of Economic Potential Of People In Pandemic Through Earning Zakat Distribution

Abstract: Purpose: This research aimed to ascertain the people's economic progress throughout the pandemic via the distribution of productive zakat by BAZ/LAZ in Pekalongan.   Theoretical Framework: Zakat has evolved as a tool for economic growth and poverty reduction among the peoples of the regions during times of economic distress (Yusroni & Chadhiq, 2021). Zakat provides several benefits over the standard fiscal tools now available. Numerous ideas and theories have been advanced by specialists to address the iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
11
1
1
Order By: Relevance
“…Ternate City's poor are not directly affected. These results, in contrast to the results of the study Arwani, et al (2022) found that productive zakat programs with models that vary according to creativity and innovation to develop the economy and populist society in Pekalongan to avoid poverty. A populist economic development model with the main objective of saving, donating, and developing companies to get out of poverty.…”
Section: Dcontrasting
confidence: 99%
“…Ternate City's poor are not directly affected. These results, in contrast to the results of the study Arwani, et al (2022) found that productive zakat programs with models that vary according to creativity and innovation to develop the economy and populist society in Pekalongan to avoid poverty. A populist economic development model with the main objective of saving, donating, and developing companies to get out of poverty.…”
Section: Dcontrasting
confidence: 99%
“…By providing training programs and workshops on governance best practices, financial management, and ethical considerations, zakat institutions can enhance their capabilities and ensure the effective management of zakat funds. 25 The findings from qualitative interviews and focus group discussions highlight the significance of zakat empowerment initiatives in generating sustainable socio-economic impact. Zakat recipients express gratitude for programs that provide them with valuable skills training, access to microfinance support, and opportunities for entrepreneurship.…”
Section: Resultsmentioning
confidence: 98%
“…Nwani (2021) employing a system generalised method of moments (SGMM) concluded that for the period 1985 to 2019 human capital has an adverse effect on growth in South Asia and sub-Saharan Africa region. Arwani et al, (2023) concluded that human development index did not significantly impact growth in Central Java Province for the period 2015-2020.…”
Section: Theoretical Frameworkmentioning
confidence: 98%